Book Review: The EU’s Impact on Identity Formation in East-Central Europe between 2004 and 2013: Perceptions of the Nation and Europe in Political Parties of the Czech Republic, Poland, and Slovakia - Ferrero-Turrión, Ruth (Studies of Transition States and Societies, 2022)
The EU’s Impact on Identity Formation in East-Central Europe between 2004 and 2013: Perceptions of the Nation and Europe in Political Parties of the Czech Republic, Poland, and Slovakia by Michal Vit, 2020, Ibidem-Verlag